Bank bailouts, interventions, and moral hazard - Lammertjan Dam; Michael Koetter (Deutsche Bundesbank, 2011)
To test if safety nets create moral hazard in the banking industry, we develop a simultaneous structural two-equations model that specifies the probability of a bailout and banks' risk taking.We identify the effect of expected bailout probabilities on risk taking using exclusion restrictions based on regional political, supervisor, and banking market traits. The sample includes all observed capital preservation measures and distressed exits in the German banking industry during 1995-2006. The marginal effect of risk with respect to bailout expectations is 7.2 basis points. A change of bailout expectations by two standard deviations increases the probability of official distress from 6.2% to 9.9%. Only interventions directly targeting bank management and, to a lesser extent, penalties mitigate moral hazard. Weak interventions, such as warnings, do not reduce moral hazard.
Keywords: C30; C78; G21; G28; L51; 330; Banking; supervision; moral hazard; intervention; bailouts; Bankrisiko; Schuldenübernahme; Moral Hazard; Bankenaufsicht; Schätzung; Deutschland